2008
DOI: 10.1007/s10549-008-9999-z
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer characteristics at diagnosis and survival among Arab–American women compared to European– and African–American women

Abstract: Background-Data from Arab world studies suggest that Arab women may experience a more aggressive breast cancer phenotype. To investigate this finding, we focused on one of the largest settlements of Arabs and Iraqi Christians (Chaldeans) in the US, metropolitan Detroit-a SEER reporting site since 1973.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…They addressed that these biomarkers, found through differences characteristic, are useful for better treatment, and surgical or radio or hormone therapy 4548…”
Section: Surveillance Epidemiology and End Resultsmentioning
confidence: 99%
“…They addressed that these biomarkers, found through differences characteristic, are useful for better treatment, and surgical or radio or hormone therapy 4548…”
Section: Surveillance Epidemiology and End Resultsmentioning
confidence: 99%
“…However, this finding is not unique insofar as other reports have observed similarly poorer outcomes affecting African Americans with breast cancer, soft tissue sarcoma, and gynecologic malignancies. [18][19][20][21] Further investigations are necessary to determine whether these differences are a result of tumor biology, differences in screening and access to care, the type of care received, or other factors or combinations of factors. One of the limitations of the current study is that only those patients with primary, nonmetastatic small cell carcinoma of the lung for the years 1988 through 1997 were included as the analyzable population, because for the periods before and after, the use of whole-brain radiotherapy was not recorded in the SEER database.…”
Section: Discussionmentioning
confidence: 99%
“…One understudied ethnic minority group of women is Arab-Americans, in part because traditionally they have often been grouped with Caucasians. The largest concentration of Arab-Americans outside of the Middle East is in Metropolitan Detroit, MI [6]. Schwartz et al [7] found that these women in Metropolitan Detroit were less likely to have ever had a mammogram than all Michigan women and had a lower prevalence of mammography compared to other racial/ethnic groups.…”
Section: Introductionmentioning
confidence: 99%